ANALISIS DETERMINAN KUALITAS PENDOKUMENTASIAN ASUHAN KEPERAWATAN BERBASIS SIMRS KHANZA DI RUMAH SAKIT - Mira Agusthia; Rachmawaty M. Noer; Rahmawati Zartika (LPPM Universitas Awal Bros, 2026)
Nursing care documentation is a vital component of nursing services that functions as a communication tool, legal evidence, and an indicator of service quality. The implementation of a Hospital Management Information System (SIMRS) is expected to enhance the effectiveness and quality of documentation. However, several obstacles remain in its execution. Nurses tend to prioritize patient care, resulting in documentation being completed only at the end of a shift. Furthermore, SIMRS features that are not yet effective, efficient, or compliant with standards cause nurses to perform repetitive, inaccurate, and inconsistent documentation. Other constraining factors include inadequate computer facilities, unstable internet connections, and a lack of regular supervision and training. This study aims to identify the factors influencing the quality of nursing care documentation within the Khanza Management Information System at RSUD Embung Fatimah, Batam City. This research used a quantitative design with a correlational analytic approch with a cross-sectional method. Data analysis was conducted using the Chi-Square test. The sample was selected using a total sampling technique consisting of 50 staff nurses. Data analysis was performed univariate and bivariate analyses with a significance level of α= 0.05. The results showed that 25 respondents (50%) had a light workload. Bivariate analysis revealed a significant relationship between workload and the quality of nursing care documentation in the Khanza system, with a p-value of 0.000 (≤ 0.05). Additionally, there was a significant relationship between organizational support and the quality of nursing care documentation, with a p-value of 0.029 (≤ 0.05). In conclusion, workload and organizational support are related to the quality of nursing care documentation within the Khanza system at RSUD Embung Fatimah, Batam City.